Pregnancy history and current use of contraception among women of reproductive age in Burundi, Kenya, Rwanda, Tanzania and Uganda: analysis of demographic and health survey data. Issue 3 (10th March 2016) - Bakibinga, Pauline; Matanda, Dennis J; Ayiko, Rogers; Rujumba, Joseph; Muiruri, Charles; Amendah, Djesika; Atela, Martin
Abstract : Objective: To examine the relationship between pregnancy history and the use of contraception among women of reproductive age (15–49 years) in East Africa. Methods: Demographic and Health Surveys data from Burundi (2010), Kenya (2008–2009), Rwanda (2010), Tanzania (2010) and Uganda (2011) were used in the analysis. Logistic regression was used to determine the effects of women's pregnancy history on their use of contraception. Setting: Burundi, Kenya, Rwanda, Tanzania and Uganda. Participants: 3226, 2377, 4396, 3250 and 2596 women of reproductive age (15–49 years) from Burundi, Kenya, Rwanda, Tanzania and Uganda, respectively, were included in the analysis. Results: Women who had experienced a mistimed pregnancy were more likely to use a modern contraceptive method during their most recent sexual encounter in Kenya, Rwanda, Burundi and Uganda. Other significant correlates of women's contraceptive use were: desire for more children, parity, household wealth, maternal education and access information through radio. In-country regional differences on use of modern contraceptive methods were noted across five East African countries. Conclusions: Women's birth histories were significantly associated with their decision to adopt a modern contraceptive method. This highlights the importance of considering women's birth histories, especially women with mistimed births, in the promotion of contraceptive use in East Africa. Variations as a result of place of residency, educational attainment, access to family planning information and products, and wealth ought to be addressed in efforts to increase use of modern contraceptive methods in the East African region.